Growth Response of Green Mustard (Brassica juncea L.) to Application of Kasgot Fertilizer in River Sediment Soil Media: Respon Pertumbuhan Sawi Hijau (Brassica juncea L.) terhadap Aplikasi Pupuk Kasgot pada Media Tanah Endapan Sungai - Prestiani; Dwi Haryanta; Dina Chamidah (Agrotechnology Study Program, Faculty of Agriculture, Wijaya Kusuma Surabaya University, 2026)
This study aimed to analyze the effect of different doses of kasgot fertilizer on the growth of green mustard (Brassica juncea L.) cultivated in river sediment soil using a Completely Randomized Design (CRD) with six fertilizer dose levels (0–50%) and five replications. The observed parameters included plant height, stem diameter, number of leaves, leaf area, and fresh weight. The results showed that kasgot fertilizer had a significant effect on several growth parameters, particularly plant height at 10–15 days after planting (DAP), stem diameter at 15–30 DAP, number of leaves at 20–30 DAP, and leaf area at 5–20 DAP, with the K3 treatment (30% kasgot + 70% river sediment soil) producing the best vegetative growth response. However, kasgot application did not significantly affect fresh weight at harvest, indicating that the sufficient nutrient availability in river sediment soil limited the plant response to additional fertilizer. Overall, although the K3 dose effectively enhanced vegetative growth, statistically the application of kasgot fertilizer did not have a significant effect on the final biomass of green mustard plants.